DIRECT VS INDIRECT CORRECTIVE FEEDBACK FOR WRITING IMPROVEMENT: STUDENTS’ PREFERENCES - Khilda Husnia Abidah; Elisa Ratih (Wiralodra English Journal, 2022)
This research presents the students’ preference for feedback in deciding what specific feedback will be valuable and positively affect the students’ writing performance. There might be a mismatch between students’ preferences and lecturer’s practice from a few past studies. A quantitative research design was utilized in this study. It was conducted in Muhammadiyah Malang University with 70 English Language Education Department students as the participants. A data set of 10 questions in the survey for students was adjusted from Aridah et al. (2017). Further, the data were scored using the “Feedback Scale” with a scale ranging from 0 to 1. The finding showed that the feedback preference of the students is direct corrective feedback, in which the mean score was higher (M=6.53) than indirect corrective feedback. The students believed that direct corrective feedback gave more additional clearness. Therefore, this study recommended that the lecturer give feedback based on the students’ preference which is direct corrective feedback to improve their writing skills easily and effectively.